Climate, Grapevine Phenology, Wine Production, and Prices: Pauillac (1800–2009) - Chevet, Jean-Michel; Lecocq, Sébastien; Visser, Michael (American Economic Review, 2011)
This paper analyzes 19th and 20th century data from a well-known château in Bordeaux. The dataset includes information on weather conditions, starting dates of three phenological stages of grapevine, prices, and yields. We discuss how these variables have evolved over the last two centuries. We also study to what extent the impact of climate on yields and prices has changed over time. Our regression analysis suggests that the effect of temperature on yields has become weaker since the 19th century. The influence on prices has, on the contrary, become stronger.